2023
DOI: 10.1186/s12909-023-04229-w
|View full text |Cite
|
Sign up to set email alerts
|

Remote, asynchronous training and feedback enables development of neurodynamic skills in physiotherapy students

Abstract: Background During the COVID-19 pandemic, face-to-face teaching and learning of physiotherapy practical skills was limited. Asynchronous, remote training has been effective in development of clinical skills in some health professions. This study aimed to determine the effect of remote, asynchronous training and feedback on development of neurodynamic skills in physiotherapy students. Methods Longitudinal repeated measurements study, across four trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
3
1
3
Order By: Relevance
“…In a study of remote asynchronous training to develop the neurodynamic skills of PT students, it was found that 2-3 sessions could achieve the target standard [31]. It is very similar to the nature of our study course and also focuses on the development of practical skills, but they still achieved the teaching goal, which is somewhat incongruent with our study.…”
Section: General Attitude Is Negative Especially In Terms Of Practica...contrasting
confidence: 53%
See 3 more Smart Citations
“…In a study of remote asynchronous training to develop the neurodynamic skills of PT students, it was found that 2-3 sessions could achieve the target standard [31]. It is very similar to the nature of our study course and also focuses on the development of practical skills, but they still achieved the teaching goal, which is somewhat incongruent with our study.…”
Section: General Attitude Is Negative Especially In Terms Of Practica...contrasting
confidence: 53%
“…In addition, it was reported that students may feel that this type of teaching would negatively affect their practical performance, which seems to be an important indicator of their satisfaction levels [31]. One student (Interview 5) commented: "If it's the theory, I can understand online classes, but for hands-on practical training, I really can't do it because it is really unacceptable", highlighting a common low satisfaction.…”
Section: The Suitability Of Curriculum Settings and Teaching Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Como respuesta a esta necesidad, se comenzaron a dictar cursos en modalidad en línea, bajo el concepto de entrenamiento remoto, en el cual el instructor y el alumno se comunicaban de manera asincrónica. 6 El Centro de Simulación de la Pontificia Universidad Católica de Chile instauró una plataforma digital llamada C1DO1 "see one, do one", la cual permite dictar cursos de manera remota y asincrónica, donde el alumno revisa un video tutorial, practica la habilidad, graba un intento y posteriormente un docente experto corrige el video anteriormente cargado en esta plataforma. 6 Dentro de los cursos que se han aplicado exitosamente están los de suturas básicas, laparoscopia básica y laparoscopia avanzada, los que han demostrado adquisición y retención de habilidades.…”
Section: Evolución De La Simulación En Educación Médica: Contexto Act...unclassified